Bailey's Industrial Oil and Fat Products 2005
DOI: 10.1002/047167849x.bio025
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lipids and Health

Abstract: Lipids are essential components of living organisms and support multiple biological and physiological functions in the human body. They serve as the structural building material of all membranes of cells and organelles. Lipids and their derivatives also serve as signaling molecules that facilitate a variety of physiological functions. In addition, lipids are recognized as important biomarkers of disease and are involved in several pathological conditions. Individual fatty acids can influence biological process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 148 publications
0
2
0
Order By: Relevance
“…Fat is one of the most important ingredients used in cookie manufacture, being the third largest component after flour and sugar, and is the most important contributor to the caloric value of cookies. High fat intake has been associated with cardiovascular disease, among other pathologies (Watkins et al, 2005). It has been reported that lauric acid decreases the total/HDL cholesterol ratio, due to a larger increase in HDL cholesterol (Mensink et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Fat is one of the most important ingredients used in cookie manufacture, being the third largest component after flour and sugar, and is the most important contributor to the caloric value of cookies. High fat intake has been associated with cardiovascular disease, among other pathologies (Watkins et al, 2005). It has been reported that lauric acid decreases the total/HDL cholesterol ratio, due to a larger increase in HDL cholesterol (Mensink et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, the conversion rate of ALA to DHA is too low to be considered efficient from a nutritional point of view [23]. Therefore, there is a need to increase the intake of foods with n-3 PUFAs [24].…”
Section: Introductionmentioning
confidence: 99%